Ziemiański mecenat archeologiczny w Wielkim Księstwie Poznańskim: Adolf Skarbek-Małczewski (1813-1887) z Kruchowa koło Trzemeszna, odkrywca słynnego aquamanile - Fogel, Jerzy (Folia Praehistorica Posnaniensia, 2018)
A name of Adolf Skarbek-Malczewski brings back a discovery of the famous Roman aquamanile in his estate at Kruchowo near Trzemeszno in 1852. The article provides a detailed account on numerous field works by A. Malczewski, their repercussions in a subject literature along with significant museological enterprises of the period (the Warszawa exhibition in 1856/1857, the Kraków exhibition in 1858/1859). This part is followed by an attempt to reconstruct a private archaeological collection of A. Skarbek-Malczewski.